Studi Perbandingan SNI Baja terhadap Metode Perhitungan Kekuatan Aksial Tekan pada Elemen Komposit Tabung Baja Berpengisi Beton - Amalia, Aniendhita Rizki; Irawan, Djoko; Iranata, Data (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
This article provides information regarding the comparison of methods and results for calculating compressive strength in compression member composite elements of concrete filled steel tubes (CFST) based on three standards (SNI) related to the design and specifications of structural steel in buildings. The three standards being compared are SNI 03-1729-2002, SNI 1729-2015 and SNI 1729:2020. Hollow structural sections (HSS) are widely used as structural elements, then increase their strength and reliability, concrete is added as a filler, known as Concrete Filled Steel Tubes (CFST) Sections. In all three standards, there are the same concept and discussion. Meanwhile, different methods, formulas, and coefficients appear in the calculation of compressive axial strength for CFST, so there are different results. The design axial strength values based on SNI 1729-2015 and SNI 1729:2020 are coincide, even though there are different coefficients. Further, the calculation results of the two SNIs are smaller than SNI 03-1729-2002 due to significant change in the suggested reduction factor. Overall, based on this study, the existing CFST member designed using SNI 03-1729-2002 needs to be re-evaluated, especially in their axial force restraining contribution.